2019
DOI: 10.1038/s41598-019-52839-6
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone Modulates the Vascular Contractility in Hypertension by Interference with ET-1 Pathway

Abstract: Endothelin-1 (ET-1) is an important modulator of the vascular tone and a proinflammatory molecule that contributes to the vascular damage observed in hypertension. Peroxisome-proliferator activated receptors-γ (PPARγ) agonists show cardioprotective properties by decreasing inflammatory molecules such as COX-2 and reactive oxygen species (ROS), among others. We investigated the possible modulatory effect of PPARγ activation on the vascular effects of ET-1 in hypertension. In spontaneously hypertensive rats (SHR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…Following the investigation of other inflammatory effects on the BBB caused by TNFα, we found increased expression of Cox-2, VCAM-1 and ICAM-1 and increased secretion of IL-6, IL-8 and MCP1, with pioglitazone being capable of reversing the effects seen for VCAM-1, ICAM-1 and MCP1 only. At first, some of these are seemingly contradicting effects, as pioglitazone was reported in other studies to reduce levels of both interleukins and Cox-2 alongside VCAM-1 and ICAM-1, but these were reported under different conditions in different body compartments [ 36 , 37 , 38 , 39 ]; these results, while being reported on endothelial cells, are still far from the BBB model here used. As there are no studies on the actions of pioglitazone on inflammatory effects on the BBB for the sake of comparison, it is reasonable to assume, under the conditions here employed, that pioglitazone does not modulate inflammation in all of its aspects in the BBB.…”
Section: Discussionmentioning
confidence: 79%
“…Following the investigation of other inflammatory effects on the BBB caused by TNFα, we found increased expression of Cox-2, VCAM-1 and ICAM-1 and increased secretion of IL-6, IL-8 and MCP1, with pioglitazone being capable of reversing the effects seen for VCAM-1, ICAM-1 and MCP1 only. At first, some of these are seemingly contradicting effects, as pioglitazone was reported in other studies to reduce levels of both interleukins and Cox-2 alongside VCAM-1 and ICAM-1, but these were reported under different conditions in different body compartments [ 36 , 37 , 38 , 39 ]; these results, while being reported on endothelial cells, are still far from the BBB model here used. As there are no studies on the actions of pioglitazone on inflammatory effects on the BBB for the sake of comparison, it is reasonable to assume, under the conditions here employed, that pioglitazone does not modulate inflammation in all of its aspects in the BBB.…”
Section: Discussionmentioning
confidence: 79%
“…In a study that used a hypertensive rat model, pioglitazone was shown to activate peroxisome-activated receptors (PPARs) by regulating endothelin-1 (ET-1) expression to attenuate the effects of oxidative stress on the vasculature. In addition, pioglitazone may improve vasodilatory function by increasing ET-1 receptor B (ETB) expression to release endothelial cell relaxing factors ( 81 ). The PROspective pioglitAzone Clinical Trial In macroVascular Events (PROactive trial) was the first large RCT to evaluate the effects of pioglitazone monotherapy on cardiovascular outcomes, and the results showed that pioglitazone reduced the risks of all-cause mortality, nonfatal heart attack, and stroke in patients with T2DM with macrovascular disease ( 82 ).…”
Section: Discussionmentioning
confidence: 99%
“…PPARγ not only regulates hypoxia-induced ET-1 levels but also other components of the ET-1 signaling pathway, such as Endothelin-Converting Enzyme 1 (ECE-1) mRNA levels, ETA, and ETB (21). Due to the above, it is believed that PPARγ agonists could reverse pulmonary vascular remodeling (22,23). Furthermore, a malfunction of BMPR2 has been shown to decrease endogenous PPARγ activity and promote metabolic pathways associated with vascular remodeling (24).…”
Section: Discussionmentioning
confidence: 99%